Distinguishing appropriate from inappropriate conditions on research participation - Steel, Robert (Bioethics, 2023)
Individuals do not have a right to participate in clinical trials. But, they do have a right against being denied participation for inappropriate reasons. Despite the widespread endorsement of these two claims, there has been little discussion regarding which conditions for participation in clinical trials are appropriate and which are inappropriate. The present manuscript attempts to address this gap in the literature. We first describe and then argue against the claim that conditions on enrollment or continued participation are appropriate only when they are needed to answer the scientific question(s) posed by the trial. We then offer an alternative view according to which the appropriateness of conditions depends on whether they help to satisfy the ethical requirements of clinical research. Because these requirements include social value, the present view implies that promoting social value is an acceptable reason to impose conditions on research participation. With this in mind, we explain why it is not coercive to require potential participants to accept conditions on enrollment that promote a trial's social value, even when the participants find those conditions unwelcome. We conclude by evaluating the present proposal's implications for the common practice of requiring participants to agree to the possible use of their leftover biospecimens in a broad range of future research. We argue, contra current regulatory policy, that this practice can be acceptable even when the present trial offers participants the prospect of clinical benefit and the samples are being reserved for future research that is unrelated to the present trial.